Morphological, pedigree, and molecular distances and their association with hybrid wheat performance - Bertan, Ivandro; Carvalho, Fernando Irajá Félix de; Oliveira, Antonio Costa de; Benin, Giovani; Vieira, Eduardo Alano; Valério, Igor Pirez (Pesquisa Agropecuaria Brasileira, 2010)
The objectives of this work were to estimate the genetic distance among wheat genotypes using morphological, pedigree, molecular, and combined morphological and molecular measures, to determine the correlations between these measures, and to evaluate the combining ability of the genotypes. Three generations and two planting designs were studied. Six wheat genotypes were crossed using a diallel design. The F1, F2 and F3 generations were evaluated in the field, in the crop seasons of 2003, 2004 and 2005, under spaced plant and full-row planting designs. The estimated general and specific combining abilities of tested hybrids were influenced both by the generation and the planting design. The correlation coefficients among the distance measures and between these measures and genotype performances of different generations for the two planting designs were low to moderate. In order to obtain a more precise estimate of the genetic distance among cultivars and its association with the hybrid performance, more than one generation, planting design, and genetic distance estimation technique should be employed.